Pengaruh Model Pembelajaran Koooperatif Tipe Think Talk Write Terhadap Kemampuan Komunikasi Matematis Peserta Didik Kelas VIII SMPN 1 Lubuk Alung - ENES ZAKIYA (Departemen Matematika, 2019)
The mathematical communication skill is an important aspect and should be achieved in the learning of mathematics. The Importance of mathematical communication skill for students make this capability need to be improved in the learning process of mathematics. The observation results indicate that the mathematical communication skill of the students in SMPN 1 Lubuk Alung was still low. The method that can be applied to improve the mathematical communication skill of students is by applying cooperative learning Think Talk Write model. The type of research was quasy-experimental and descriptive with the randomized control group only design. The results of this research showed that the development of mathematical communication skill of students whose during learning process using TTW model has increased, and mathematical communication skill of students whose learning process using TTW model is better than mathematical communication skill of students whose learning with direct learning.Keywords – Mathematical Communication Skill, Cooperative Learning Model, Think Talk Write.